Products and activities associated with non-fatal traumatic brain injuries in children and adolescents – United States 2010-2013. (19th September 2019) - Ali, Bina; Lawrence, Bruce A.; Miller, Ted; Allison, Jennifer
ABSTRACT: Background : Traumatic brain injury (TBI) is prevalent in children and adolescents ages <1–19 years, yet we have limited understanding of consumer products that are associated with TBIs in children and adolescents of varying ages. To address this gap, we combined two data sources to investigate leading products and activities associated with TBIs in children and adolescents in different developmental age groups (i.e. <1, 1–4, 5–9, 10–14, and 15–19 years). Methods : We analysed data from the National Electronic Injury Surveillance System–All Injury Program (NEISS-AIP), augmented with product information from the National Electronic Injury Surveillance System (NEISS), for the years 2010 through 2013. Results : From 2010 to 2013, children and adolescents aged <1–19 years accounted for 4.1 million non-fatal TBI-related emergency department visits. TBIs from home furnishings and fixtures, primarily beds, were highest among infants aged <1 year and children aged 1–4 years. TBIs from sports/recreation, especially bicycles and football, were highest among those aged 5–9 years, 10–14 years, and 15–19 years. Conclusions : The combined NEISS and NEISS-AIP data allow us to comprehensively examine products and activities that contribute to emergency department visits for TBIs in children and adolescents. Our findings indicate priority areas for TBI prevention and intervention.